Aquaporin 11-dependent inhibition of proliferation by deuterium oxide in activated hepatic stellate cells - Lee, Phil Jun; Park, Hye Jin; Cho, Namki; Kim, Hong Pyo (Molecules, 2018)
Deuterium oxide (D2O) has been reported to be active toward various in vitro cell lines in combination with phytochemicals. Our objective was to describe, for the first time, the effect of D2O on the proliferation of hepatic stellate cells (HSCs). After D2O treatment, the p53-cyclin-dependent kinase (CDK) pathway was stimulated, leading to inhibition of the proliferation of HSCs and an increase in the [ATP]/[ADP] ratio. We also evaluated the role of aquaporin (AQP) 11 in activated HSCs. We found that D2O treatment decreased AQP11 expression levels. Of note, AQP11 levels elevated by a genetic approach counteracted the D2O-mediated inhibition of proliferation. In addition, the expression levels of AQP11 negatively correlated with those of p53. On the other hand, cells transfected with an AQP11-targeted small interfering RNA (siRNA) showed enhanced inhibition of proliferation. These findings suggest that the inhibition of cell proliferation by D2O in activated HSCs could be AQP11 dependent. Our previous studies have documented that bisdemethoxycurcumin (BDMC) induces apoptosis by regulating heme oxygenase (HO)-1 protein expression in activated HSCs. In the current study, we tested whether cotreatment with BDMC and D2O can modulate the AQP11-dependent inhibition of cell proliferation effectively. We observed that D2O cotreatment with BDMC significantly decreased cell proliferation compared to treatment with D2O alone, and this effect was accompanied by downregulation of HO-1 and an increase in p53 levels.
Keywords: Adenosine Triphosphate; Animals; Apoptosis; Aquaporins; Cell Cycle Checkpoints; Cell Line; Cell Line, Tumor; Cell Proliferation; Cells, Cultured; Cyclins; Deuterium Oxide; Heme Oxygenase-1; Hepatic Stellate Cells; Humans; Rats; Signal Transduction; Tumor Suppressor Protein p53; AQP11; Aquaporin 11; Bisdemethoxycurcumin; Deuterium oxide; Heme oxygenase 1; Hepatic stellate cell; HO-1